THU0068 The risk of individual autoantibodies, autoantibody combinations and autoantibody levels for arthritis development in clinically suspect arthralgia. (15th June 2017) - Brinck, RM Ten; Steenbergen, HW van; Delft, MA van; Verheul, MK; Toes, RE; Trouw, LA; Mil, AH van der Helm-van
Abstract : Background: Autoantibody testing is helpful to predict progression to arthritis in subjects at risk. Previous longitudinal studies mainly focussed on autoantibody-positive arthralgia patients. Consequently predictive values of autoantibodies were evaluated relative to each other. This study assessed risks of having anticitrullinated protein antibodies (ACPA), rheumatoid factor (RF) and/or anti-carbamylated protein antibodies (anti-CarP) for arthritis development in arthralgia patients considered at risk for RA by rheumatologists based on clinical characteristics (Clinically Suspect Arthralgia, CSA). Objectives: To assess risks of having anticitrullinated protein antibodies (ACPA), rheumatoid factor (RF) and/or anti-carbamylated protein antibodies (anti-CarP) for arthritis development in arthralgia patients considered at risk for RA by rheumatologists based on clinical characteristics (CSA). Methods: Baseline ACPA, RF and anti-CarP antibodies of 241 patients, consecutively included in the CSA-cohort, were studied in relation to development of clinical arthritis during a median follow-up of 103 (IQR 81–114) weeks. Results: ACPA, RF and anti-CarP antibodies were all univariably associated with arthritis development, hazard ratios (95% CI) were 8.5 (4.7–15.5), 5.1 (2.8–9.3) and 3.9 (1.9–7.7). Only ACPA, and not RF or anti-CarP, was independently associated (HR 5.1, 2.0–13.2). Relative to autoantibody-negative CSA-patients, ACPA-negative/RF-positive patients had HRs of 2.6 (1.04–6.6), ACPA-positive/RF-negative patients 8.0 (2.4–27.4), and ACPA-positive/RF-positive patients 10.5 (5.4–20.6, Figure). PPVs for development of clinical arthritis within two years were: 38% for ACPA-negative/RF-positive, 50% for ACPA-positive/RF-negative, and 67% for ACPA-positive/RF-positive patients. Higher ACPA-levels were not significantly associated with increased progression to clinical arthritis, in contrast to higher RF-levels. Autoantibody levels were stable during follow-up. Conclusions: ACPA conferred the highest risk for arthritis development and had an additive value to RF. However, >30% of ACPA-positive/RF-positive CSA-patients did not develop arthritis during two-year follow-up. Thus CSA and information on autoantibodies is insufficient to accurately identify imminent autoantibody-positive RA. Disclosure of Interest: None declared